2020
DOI: 10.1038/s41598-020-76887-5
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces sp. strain TOR3209: a rhizosphere bacterium promoting growth of tomato by affecting the rhizosphere microbial community

Abstract: Aiming at revealing the possible mechanism of its growth promoting effect on tomato, the correlations among Streptomyces sp. TOR3209 inoculation, rhizobacteriome, and tomato growth/production traits were investigated in this study. By analyses of Illumina sequencing and plate coating, differences in rhizosphere microbial communities were found in different growth stages and distinct inoculation treatments. The plant biomass/fruit yields and relative abundances of families Flavobacteriaceae, Sphingobacteriaceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 78 publications
3
21
3
Order By: Relevance
“…The members of the genus Streptomyces are Gram-positive, spore-forming bacteria that are widely distributed in the soil and other habitats, and they are well known for their ability to produce a large number of bioactive secondary metabolites (antibiotics) (Quinn et al, 2020 ), but rarely act as phytopathogens (Li et al, 2019 ). Recently, Streptomyces strains have been utilized as PGPR for several crops, including wheat (Akbari et al, 2020 ), tomato (Hu et al, 2020 ), chickpea (Gopalakrishnan et al, 2015 ), sorghum (Gopalakrishnan et al, 2013 ), and rice (Suárez-Moreno et al, 2019 ). The PGP effects of these Streptomyces strains have been attributed to their production of siderophores and indole-3-acetic acid, nitrogen fixation, and phosphate solubilization, which make them potential biofertilizers (Romano-Armada et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The members of the genus Streptomyces are Gram-positive, spore-forming bacteria that are widely distributed in the soil and other habitats, and they are well known for their ability to produce a large number of bioactive secondary metabolites (antibiotics) (Quinn et al, 2020 ), but rarely act as phytopathogens (Li et al, 2019 ). Recently, Streptomyces strains have been utilized as PGPR for several crops, including wheat (Akbari et al, 2020 ), tomato (Hu et al, 2020 ), chickpea (Gopalakrishnan et al, 2015 ), sorghum (Gopalakrishnan et al, 2013 ), and rice (Suárez-Moreno et al, 2019 ). The PGP effects of these Streptomyces strains have been attributed to their production of siderophores and indole-3-acetic acid, nitrogen fixation, and phosphate solubilization, which make them potential biofertilizers (Romano-Armada et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional chemical fumigation and pesticide application are highly effective in preventing and controlling ARD, but their use has harmful effects on the environment [1,8]. At present, Trichoderma, Bacillus, Pseudomonas, and Streptomyces are widely used as biological control agents [9][10][11], in line with the concept of "double reduction" of fertilizers and pesticides. Compared to rhizosphere soil strains, endophytes can more effectively colonize plants and better adapt to environmental changes, making them more effective in disease suppression and growth promotion [12].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that Streptomyces could coexist and inhibit the growth of other microbes in regulating the composition and structure of the organic network. Hu et al (2020) suggested that Streptomyces application could promote the growth of tomato by reshaping the rhizosphere microbial community and could positively increase the abundance of other beneficial bacteria. Cyanobacterial Calothrix sp.…”
Section: Discussionmentioning
confidence: 99%